Sоmе Controversy about Law on Private Security - Stajić, Ljubomir; Mandić, Goran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The Republic of Serbia is one of the last countries that legally regulate the private security sector, which is a new conceptual system of the national security system. Since the law is expected to solve many issues and dilemmas, and bring order to the area, which by some accounts is a very profitable branch of economy. Expectations were that by the end to regulate issues such as: 1) the need for institutionalization of partnership between the public and private sectors for mutual benefit, 2) the need of expressing mutual interest to establish the desired condition of security in the entire society and 3) the need to define the mechanisms and authority to achieve mentioned above. Based on this, legal framework of private security should explicitly provide: 1) a new role of the private sector, 2) communication and data exchange between the public and private sector, 3) mandatory notification about prepared or committed criminal acts on which there is information, 4) cooperation in the tasks of necessarily protected facilities, 4) cooperation in crisis situations including natural disasters, traffic accidents, strikes, sabotage, terrorist attacks, etc., 5) cooperate in the selection and training of staff and 6) cooperation in planning activities and project design of security. This paper presents a critical review of some theoretical and professional controversies in the solutions provided by law, for the purpose of answering whether it is achieving the purpose of passing of such a legal act.